The Effect Of Advertising, Brand Image And Lifestyle On Purchasing Decisions For Honda Scoopy Motorcycles: (Case Study of Honda Scoopy Motor Bikers in Bengkalis) - Dewi Azzira; Nageeta Tara Rosa (Politeknik Kampar, 2025)
This study aims to analyze the effect of advertising, brand image and lifestyle on purchasing decisions for Honda Scoopy motorbikes in Bengkalis. This study uses a quantitative method using a non-probability sampling method with purposive sampling. The sample in this study were 100 respondents, data processing using the IBM SPSS version 27 application with multiple linear regression analysis testing which includes validity test, reliability test, T test, F test, and coefficient of determination (R2). The results of this study indicate that: 1) Advertising has a positive and significant effect on purchasing decisions for Honda Scoopy motorbikes in Bengkalis, 2) Brand Image has a positive and significant effect on Purchasing Decisions for Honda Scoopy Motorbikes in Bengkalis, 3) Lifestyle has a positive and significant effect on the Honda Scoopy Motorcycle Purchasing Decision in Bengkalis, 3) the coefficient of determination (R2) is 0.565. This means that advertising, brand image and lifestyle affect the purchase decision of a Honda Scoopy motorcycle in Bengkalis by 56.5%, while the remaining 43.5% is influenced by other variables not examined in this study.